2017
DOI: 10.1038/srep41778
|View full text |Cite
|
Sign up to set email alerts
|

Early life antibiotic exposure affects pancreatic islet development and metabolic regulation

Abstract: Childhood antibiotic exposure has been recently linked with increased risk of metabolic disease later in life. A better understanding of this association would potentially provide strategies to reduce the childhood chronic disease epidemic. Therefore, we explored the underlying mechanisms using a swine model that better mimics human infants than rodents, and demonstrated that early life antibiotic exposure affects glucose metabolism 5 weeks after antibiotic withdrawal, which was associated with changes in panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 81 publications
3
23
0
Order By: Relevance
“…In mice, some previous studies have indicated that low‐dose antibiotic exposure in early life may have a long‐term effect on host metabolism . In pigs, antibiotic exposure in early life altered glucose metabolism 35 days after antibiotic withdrawal . Our studies also showed that in‐feed antibiotics treatment in early life had a long‐term effect on serum urea level and fecal AA fermentation products .…”
Section: Introductionsupporting
confidence: 69%
“…In mice, some previous studies have indicated that low‐dose antibiotic exposure in early life may have a long‐term effect on host metabolism . In pigs, antibiotic exposure in early life altered glucose metabolism 35 days after antibiotic withdrawal . Our studies also showed that in‐feed antibiotics treatment in early life had a long‐term effect on serum urea level and fecal AA fermentation products .…”
Section: Introductionsupporting
confidence: 69%
“…cDNA was synthesized using Maxima First Strand cDNA Synthesis Kit (Thermo Fisher Scientific). Quantitative real‐time polymerase chain reaction (PCR) was performed as previously described using primers listed in Table S2. Data were analysed using the comparative CT (2 −ΔΔCT ) method as described previously using glyceraldehyde phosphate dehydrogenase as the housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, increased propensity for obesity and metabolic disease is now associated with early life antibiotics . In a previous study, early life antibiotic exposure in piglets altered metabolic regulation with a standard diet, however failed to change fat deposition . It was expected that the lack of difference in adiposity was due to the absence of a dietary challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation of well-balanced (homeostatic) microbial populations is known to have long-term adverse effects on host physiology [ 4 , 5 , 6 , 7 ]. For example, antibiotic perturbation of the piglet GIT microbiota in early life has been shown to be associated with impaired gut microbiome development and altered metabolic regulation later in life [ 8 ]. Furthermore, compromised resistance against infectious agents has been reported in pigs raised under more hygienic and controlled conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%